Indonesia Construction Service Law Relating to MRT Development Contracts: A Legal Review with Fidic International Contract - Suherman; Mayangsari, Annisa (International Journal of Criminology and Sociology, 2022)
This research was very important because of incomplete regulations related to Late Payment Arrangements and Variation Procedure Arrangements which are regulated in the Construction Services Law because this was very necessary considering the complexity of problems that occur in the construction world in Indonesia. The amendments to the Implementing Regulations also needed to be improved as regulated in Article 51 of Presidential Regulation N0. 54 of 2010 concerning lump sum contracts, there were no price adjustments and additional work, because in fact any construction work for price adjustment and additional work almost always occurred and almost impossible to avoid. So that these regulations could not be applied in the field and could hinder the implementation of construction project work in Indonesia. It was because most of the construction projects in Indonesia required cooperation with foreign investors.